DEVELOPMENT OF BIRDWATCHING ECOTOURISM IN GILI MENO - Ahyadi, Hilman; Sudarma, I Made; Suana, I Wayan (Jurnal Lembaga Penelitian Universitas Mataram, 2014)
Mangrove forests around Lake Meno have a great potential to be developed as a tourist area, especially birdwatching. The people in Gili Meno have a high dependence on mangrove forests, mainly for firewood, causing its damage continually increased. Development of tourism infrastructure is also contributed to the problem of land use. This is because of no clarity in land use plan. Degradation of mangrove forests is a threat in the effort to develop of birdwatching ecotourism in Gili Meno, as well as threaten environmental sustainability. This is an action research, through Participatory Rural Aprecial method, aims to: 1) make a strategic plan of management of birdwatching ecotourism, in Gili Meno, 2) improve the quality of human resources as a birdwatching guides, and 3) improve the quality of natural resources as bird habitat. The study resulted in strategic plan of management of birdwatching ecotourism, that involving relevant stakeholders. It is hope that no conflict of interest in the land utilization. A total of 3,000 mangrove seedlings have also been successfully grown. Birdwatch training has also been successful in increasing knowledge and skills of Meno Lestaris Clubs in conducting birdwatch in the field. A total of 25 species of birds have been well identified by this club.